Unlocking the secrets of galectins: a challenge at the frontier of glyco-immunology - Rabinovich, Gabriel Adrián (2002)
Over the last decade, we have witnessed an explosion of information regarding the function of glycoconjugates, carbohydrate-binding proteins, and the elucidation of the sugar code. This progress has yielded not only important insights into fundamental areas of glycobiology but has also influenced other fields such as immunology and molecular medicine. A family of galactoside-binding proteins, called galectins, has emerged recently as a novel kind of bioactive molecules with powerful, immunoregulatory functions. Different members of this family have been shown to modulate positively or negatively multiple steps of the inflammatory response, such as cell-matrix interactions, cell trafficking, cell survival, cell-growth regulation, chemotaxis, and proinflammatory cytokine secretion. To introduce a comprehensive overview of these new advances, here we will explore the molecular mechanisms and biochemical pathways involved in these functions. We will also examine the role of these proteins in the modulation of different pathological processes, such as chronic inflammation, autoimmunity, infection, allergic reactions, and tumor spreading. Understanding the intimate mechanisms involved in galectin functions will help to delineate selective and novel strategies for disease intervention and diagnosis.